Elimination of Omega-1,2 Gliadins From Bread Wheat (Triticum aestivum) Flour: Effects on Immunogenic Potential and End-Use Quality - Altenbach, Susan B.; Chang, Han-Chang; Yu, Xuechen B.; Seabourn, Bradford W.; Green, Peter H.; Alaedini, Armin (Frontiers in Plant Science, 2019)
The omega-1,2 gliadins are a group of wheat gluten proteins that contain immunodominant epitopes for celiac disease and also have been associated with food allergies. To reduce the levels of these proteins in the flour, bread wheat (Triticum aestivum cv. Butte 86) was genetically transformed with an RNA interference plasmid that targeted a 141 bp region at the 5’ end of an omega-1,2 gliadin gene. Flour proteins from two transgenic lines were analyzed in detail by quantitative two-dimensional gel electrophoresis and tandem mass spectrometry. In one line, the omega-1,2 gliadins were missing with few other changes in the proteome. In the other line, striking changes in the proteome were observed and nearly all gliadins and low molecular weight glutenin subunits (LMW-GS) were absent. High molecular weight glutenin subunits (HMW-GS) increased in this line and those that showed the largest increases had molecular weights slightly less than those in the non-transgenic, possibly due to post-translational processing. In addition, there were increases in non-gluten proteins such as triticins, purinins, globulins, serpins and alpha-amylase/protease inhibitors. Reactivity of flour proteins with serum IgG and IgA antibodies from a cohort of celiac disease patients was reduced significantly in both transgenic lines. Both mixing time and tolerance were improved in the line without omega-1,2 gliadins while mixing properties were diminished in the line missing most gluten proteins. The data suggest that biotechnology approaches may be used to create wheat lines with reduced immunogenic potential in the context of gluten sensitivity without compromising end-use quality.